Neuroimaging in Blast-Related Mild Traumatic Brain Injury. Issue 1 (January 2017) - Mu, Weiya; Catenaccio, Eva; Lipton, Michael L.
Abstract : Objective: To summarize imaging findings in blast-related mild traumatic brain injury. Design: Our structured review of the literature yielded 5 structural magnetic resonance imaging (sMRI), 18 diffusion tensor imaging, 9 functional magnetic resonance imaging (fMRI), 3 positron emission tomography, 4 magnetoencephalography, 2 electroencephalography, and 1 single-positron emission computerized tomography studies. Results: Four of the 5 sMRI studies reported decreased cortical thickness and decreased thalamus and amygdala volume. Diffusion tensor imaging studies showed abnormal diffusion within white matter tracts commonly associated with traumatic brain injury, including the corpus callosum (8 of the 18) and superior longitudinal fasciculus (8 of the 18). Resting-state fMRI studies reported a variety of functional network differences. Other functional imaging studies showed diffuse changes in activity, especially in the frontal, parietal, temporal, and cingulate regions. Conclusion: Vast variation in the sample, design, and measurement features across studies precludes salient conclusions regarding the effectiveness of neuroimaging to assess outcomes and elucidate pathomechanisms. The inherent spatial heterogeneity of mild traumatic brain injury pathology presents a major challenge to meaningful convergence across and generalizable inferences. Approaches to standardize methodology and facilitate access to data and integration across studies hold promise for enhancing our understanding of this complex brain disorder, but can only bear fruit if they are actually consistently implemented.